A New Approach to the Fine Kinney Method with AHP Based ELECTRE I and Math Model on Risk Assessment for Natural Disasters - Onur Derse (Coğrafya Dergisi)
Natural disasters impose enormous risks on human living and the environment. Researchers have given more attention to evaluating these risks in the context of disasters. Studies focus on the risk assessment of only one of the natural disasters for the regions. However, a risk assessment should be conducted that includes all-natural disasters for these regions. This risk assessment is dealt with by 8 different provinces in the Aegean region of Turkey in the work. A case data (1990-2020) on natural disasters such as earthquake, fire, landslide, flood, storm/typhoon has been considered for the cities covered. By revising the Fine Kinney risk assessment method for natural disasters, a risk score is obtained for each province. Then, the AHP based ELECTRE I method is applied to these provinces. As a result of this method, the riskiest region is obtained. The location of a crisis center in the riskiest region obtained should ensure effective solutions to the regions which are affected by the results of the disasters. Thus, the problem of choosing the most suitable location in the crisis center is handled with a goal programming approach.